Optimalisasi Karakter Gotong Royong Melalui Program Friendship Camp di PKBM Insan Cerdas Indonesia - Dwijayanto, Aditya Jati; Rosyanafi, Rofik Jalal (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The aim of this research is to describe the optimization of the friendship camp program on the character of mutual cooperation in CLC Insan Cerdas Indonesia. The research method used is case study research. Data collection techniques through participant observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, and concluding research results. The result of this research is a friendship camp program organized by CLC Insan Cerdas Indonesia starting from the planning, organizing, implementation, monitoring and evaluation stages. Planning is carried out with socialization and briefing activities. Organizing is done by forming a committee between tutors and students. The implementation was carried out for three days and two nights by strengthening the character of mutual cooperation through existing activities. Supervision is carried out by tutors. Evaluation is carried out after the friendship camp activities are carried out to see the mutual cooperation character of the students. From the program indicators, friendship camps can improve the character of mutual cooperation. This is proven by the behavior of students after participating in friendship camp activities. Keywords: Character, Mutual Cooperation, Friendship Camp